An Unusual Etiology for a 37-Year-Old Man With Paroxysmal Atrial Fibrillation and Termination Pause - Hung-Chou Yang, MD; Jo-Nan Liao, MD; Liang-Tsai Hsiao, MD, PhD; Wen-Chung Yu, MD; Shih-Ann Chen, MD (JACC: Case Reports, 2021)
This report describes a young patient with paroxysmal atrial fibrillation (AF) with termination pause. Primary mediastinal large B-cell lymphoma with pericardial and right atrial involvement was diagnosed, and he was free of AF after chemotherapy. Therefore, for young patients with tachy-brady syndrome, thorough evaluation for other causes is recommended. (Level of Difficulty: Beginner.)